Domestic firing activities and fuel consumption in a Saharan oasis: Micromorphological and archaeobotanical evidence from the Garamantian site of Fewet (Central Sahara, SW Libya). (September 2017) - Zerboni, Andrea; Mori, Lucia; Bosi, Giovanna; Buldrini, Fabrizio; Bernasconi, Andrea; Gatto, Maria Carmela; Mercuri, Anna Maria
Abstract: We describe a combined geoarchaeological and archaeobotanical approach applied to the study of firing activities that have been carried out at Fewet, a Garamantian compound in the Central Sahara (Libya), between the 3 rd century BC and the 1 st century AD. The archaeological stratigraphy of the site has been sealed by several mud-brick wall collapses, preserving an interesting sequence of living floors, whose micromorphological study is unique for the Central Sahara. This investigation together with the mineralogical analysis of sediments, confirms the field attribution of archaeological features as domestic fireplaces, and identified the living floors as areas devoted to animal penning, probably subjected to periodical firing. The investigation also highlights an exceptional concentration of gypsum pedofeatures, presumably determined by the wood type selected for fuel. The archaeobotanical study identified a good quantity of charcoal and other plant remains in the same layers. Most of the charcoal has been identified as Central Tamarix, which is the most common tree living in the oasis today. This suggests that tamarisk wood was the most exploited tree for fuel, and its combustion led to the dispersion of gypsum from the plant tissue, later recrystallized in the shape of microcrystalline nodules, lenses, and euhedral crystals. Graphical abstract: Highlights: We investigated the fire-related archaeological features and layers at ancient Fewet (central Sahara). We adopted a combined approach of geoarchaeology and archaeobotany. Micromorphology evidenced a large occurrence of gypsic pedofeatures in each layer. Charcoal analysis suggests that Tamarix was the most exploited wood for fuel. The enrichment in gypsum in firing features is related to the large consumption of Tamarix wood as fuel.